2021
DOI: 10.3390/ani11071865
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acetic Acid and Sodium Bicarbonate Supplemented to Drinking Water on Water Quality, Growth Performance, Organ Weights, Cecal Traits and Hematological Parameters of Young Broilers

Abstract: To evaluate the effect of acetic acid and sodium bicarbonate supplemented to drinking water on water quality, growth performance, relative organ weights, cecal traits and hematological parameters of broilers, a total of 456 one-day-old Cobb MV × Cobb 500 FF mixed broilers were randomly placed in three experimental treatments, with four replicates per treatment and 38 birds per replicate, for 10 days. The treatments consisted of the use of acetic acid (0.4%; T1) as acidifier, an apparently neutral pH (T2) and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…It is suggested that broilers receiving acidified water from the first days of their life would be less susceptible to colonization by enteric pathogens after exposure, due to alterations in the host gut microenvironment and the host immune system [ 59 ]. However, various parameters, including the type of acidic agents employed, dosage scheme, water quality, feed buffering capacity, feed ingredients, host microbiota composition, and general health of birds, as well as general farm management, might all have an impact on the efficacy of commercial formulas and, thereby, occasionally lead to unfavourable outcomes [ 60 , 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that broilers receiving acidified water from the first days of their life would be less susceptible to colonization by enteric pathogens after exposure, due to alterations in the host gut microenvironment and the host immune system [ 59 ]. However, various parameters, including the type of acidic agents employed, dosage scheme, water quality, feed buffering capacity, feed ingredients, host microbiota composition, and general health of birds, as well as general farm management, might all have an impact on the efficacy of commercial formulas and, thereby, occasionally lead to unfavourable outcomes [ 60 , 61 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Typhimurium infection primarily impacts this age group, compromising their growth performance, gut health, and immunity ( Alkie et al, 2019 ; Ibrahim et al, 2021 ). Impaired growth and gut health in the early broiler stage due to S. Typhimurium infection can negatively affect flock performance ( Martínez et al, 2021 ). While S .…”
Section: Introductionmentioning
confidence: 99%
“…Ascites are more typical in fastgrowing male broilers reared at high altitudes and are slightly affected by cold stress (Özkan et al, 2010). However, infectious agents such as Aspergillosis, E. coli, and bronchitis virus also induce ascites syndrome (Julian, 2000), which is known as a complication of right ventricular dysfunction (Martínez et al, 2021).…”
Section: Introductionmentioning
confidence: 99%